The upper limb of Paranthropus boisei from Ileret, Kenya. Issue 141 (April 2020) - Richmond, B.G.; Green, D.J.; Lague, M.R.; Chirchir, H.; Behrensmeyer, A.K.; Bobe, R.; Bamford, M.K.; Griffin, N.L.; Gunz, P.; Mbua, E.; Merritt, S.R.; Pobiner, B.; et al.
Abstract: Paranthropus boisei was first described in 1959 based on fossils from the Olduvai Gorge and now includes many fossils from Ethiopia to Malawi. Knowledge about its postcranial anatomy has remained elusive because, until recently, no postcranial remains could be reliably attributed to this taxon. Here, we report the first associated hand and upper limb skeleton (KNM-ER 47000) of P. boisei from 1.51 to 1.53 Ma sediments at Ileret, Kenya. While the fossils show a combination of primitive and derived traits, the overall anatomy is characterized by primitive traits that resemble those found in Australopithecus, including an oblique scapular spine, relatively long and curved ulna, lack of third metacarpal styloid process, gracile thumb metacarpal, and curved manual phalanges. Very thick cortical bone throughout the upper limb shows that P. boisei had great upper limb strength, supporting hypotheses that this species spent time climbing trees, although probably to a lesser extent than earlier australopiths. Hand anatomy shows that P. boisei, like earlier australopiths, was capable of the manual dexterity needed to create and use stone tools, but lacked the robust thumb of Homo erectus, which arguably reflects adaptations to the intensification of precision grips and tool use. KNM-ER 47000 provides conclusive evidence that early Pleistocene hominins diverged in postcranial and craniodental anatomy, supporting hypotheses of competitive displacement among these contemporaneous hominins.